Circular economy, energy transition, and role of hydrogen - Ibham Veza; Muhammad Idris; Islam Md Rizwanul Fattah (Universitas Muhammadiyah Magelang, 2022)
Circularity is not a new concept. Activities such as reuse or recycling have been around for centuries. Today, an urgent solution to tackle the increasing harmful emissions resulting in severe climate changes is being proposed and investigated. This is because a link between industry and the environment is critically important for business. A more sustainable socio-technical system is therefore urgently needed. There has been a rapid growth of academic articles on the circular economy. The circular economy concept has been considered a solution to many of today’s challenges, including resource scarcity and waste generation.